(untitled) (Construction Economics and Building, 2020)
The embracement of smart city approach as a sustainable system for the management and delivery of infrastructural developments has been on the increase, especially in developed and some developing countries. For this to be successful, cities in these countries, particularly in developing ones like South Africa, needs to be resilient because even though resilience can be achieved by making cities smart, smartness does not bring resilience by default. Thus, this study examines various factors influencing the ability of cities to develop resilience through smart city drivers. A survey of construction professionals involved in the design, planning, development and general management of cities and their infrastructure was carried out with the aid of a well-structured questionnaire. Factors influencing resilience were grouped into five divisions which are climate change, education, food security, public safety and threat to disease, in order of their importance. Findings revealed that the most important of these factors are the development of literacy and technical skills of citizens, regeneration of agricultural land and increased localised food production. The paper further examined the effects of these factors on six smart city drivers and found out that smart economy has the most influence on the resilience of a city. It was concluded that stakeholders concerned with the achievement of resilient smart city must give attention to the major needs of its citizens, and such needs are better produced locally.